2016
DOI: 10.1155/2016/7414036
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma Obtained with Different Anticoagulants and Their Effect on Platelet Numbers and Mesenchymal Stromal Cells Behavior In Vitro

Abstract: There are promising results in the use of platelet-rich plasma (PRP) for musculoskeletal tissue repair. However, the variability in the methodology for its obtaining may cause different and opposing findings in the literature. Particularly, the choice of the anticoagulant is the first definition to be made. In this work, blood was collected with sodium citrate (SC), ethylenediaminetetraacetic acid (EDTA), or anticoagulant citrate dextrose (ACD) solution A, as anticoagulants, prior to PRP obtaining. Hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 78 publications
(67 reference statements)
4
45
1
Order By: Relevance
“…It is worth noting that our PRP protocol utilized a low concentration of SC as an anticoagulant for the purification of PRP. Compared to other anticoagulants, SC has been found to have high platelet recovery and mesenchymal stromal cell proliferation which makes it an optimal anticoagulant . However, there are studies that have suggested SC can improve olfactory dysfunction in postinfectious loss .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that our PRP protocol utilized a low concentration of SC as an anticoagulant for the purification of PRP. Compared to other anticoagulants, SC has been found to have high platelet recovery and mesenchymal stromal cell proliferation which makes it an optimal anticoagulant . However, there are studies that have suggested SC can improve olfactory dysfunction in postinfectious loss .…”
Section: Discussionmentioning
confidence: 99%
“…Do Amaral et al . 122 found that there was no difference between the use of EDTA, ACD (acid citrate dextrose) and sodium citrate as an anticoagulant; however, EDTA yielded higher platelet quantity, PRP obtained by citrate solution resulted in higher induction of MSC proliferation and smallest variation in MSC gene expression and ACD caused an increase in platelet recovery. There are two widely used protocols in the preparation of PRP: one step and two step PRP preparation.…”
Section: Gfs In Prpmentioning
confidence: 97%
“…For instance, we did not compile information about activators and anticoagulants used because it was reported in less than half of the studies we analyzed. However, specific activator and anticoagulant use has been shown to affect both platelet count54 and growth factor release,55 thus it is important to report such values in future studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%